Genetic Diversity in Aus Rice Genotypes using ILP Markers - Siddique, MA; Khalequzzaman, M; Islam, MZ; Rashid, ESMH; Baktiar, MHK; Chowdhury, MAZ (Bangladesh Rice Journal, 2017)
Assessment of genetic diversity is essential for germplasm characterization, utilization and conservation. Genetic diversity of 31 Aus rice genotypes of Bangladesh was assessed using 11 ILP (intron length polymorphism) markers. A total of 28 alleles were detected and the number of alleles per locus varied from 2 (RI01779, RI05751, RI05304, RI03205, RI00299, RI05407) to 4 (RI05559). The PIC values ranged from 0.06 (RI05407) to 0.57 (RI05559) with an average of 0.33. PIC value revealed that RI05559 was the best ILP markers for the studied 31 Aus rice genotypes. The dendrogram from unweighted pair-group method with arithmetic average clustering classified the genotypes into five groups at a coefficient of 0.57. Two dimensional graphical views of Principal Coordinate Analysis (PCoA) revealed that the genotypes Kuchmuch, Kalo dhan, Aus dhan, Sadey aus, Chaina and Dighi bawalia were found far away from the centroid of the cluster and can be seslected as parents for further breeding programmes. Parangi and V3, Adubali and H1-2, Begunbichi and Hashikalmi had closest distance (0.000) in the distance matrix might have same genetic background. This information will be useful for the selection of genetically diversed parents and assist in trait development using genotypes in rice breeding programmes in future. The results provided some useful implications for establishment of sovereignty of Bangladeshi rice gene pool. It was also suggested that ILP markers could be very useful for the genetic study and breeding in rice. Bangladesh Rice j. 2016, 20(2): 13-19